Modulating room temperature spin injection into GaN towards the high-efficiency spin-light emitting diodes. (27th March 2020) - Song, Anke; Chen, Jiajun; Lan, Jinshen; Fu, Deyi; Zhou, Jiangpeng; Zhong, Zhibai; Guo, Jian; Wu, Xuefeng; Wu, Yaping; Li, Xu; Huang, Shengli; Wu, Zhiming; et al.
Abstract: Spin injection performance in GaN film was systematically investigated through the three-terminal Hanle spin precession measurements with the comparison of varied tunnel barrier thickness, spin injector materials, and channel widths. Spin relaxation time and diffusion length were optimized to 37.3 ps and 139.0 nm at room temperature, respectively. With the optimal spin injector, a 12% spin polarization was obtained in a four-terminal non-local spin valve device. By applying the optimized spin injector structure to the spin-light emitting diodes, room temperature circular polarization ratios of 6.2% and 9.2% for Co and Fe spin polarizers were respectively achieved at surface-emission.